2008
DOI: 10.1002/mnfr.200700437
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate (EGCG) attenuates high glucose‐induced insulin signaling blockade in human hepG2 hepatoma cells

Abstract: Insulin resistance is the primary characteristic of type 2 diabetes which as a result of insulin signaling defects. It has been suggested that the tea polyphenol (-)-epigallocatechin-3-gallate (EGCG) displays some antidiabetic effects, but the mechanism for EGCG insulin-enhancing effects is incompletely understood. In the present study, the investigations of EGCG on insulin signaling are performed in insulin-responsive human HepG2 cells cotreated with high glucose. We found that the high glucose condition caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
121
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 41 publications
10
121
0
1
Order By: Relevance
“…In addition, EGCG may also improve metabolic abnormalities by activating AMPK in the liver, which enhances insulin sensitivity and increases fatty acid oxidation but decreases fatty acid synthesis (32). This finding is consistent with recent studies showing that EGCG increases insulin sensitivity and fat oxidation and induces AMPK activity in the liver (36,37). Furthermore, in addition to the improvement of metabolic disorders, activation of AMPK by EGCG also positively contributes to the prevention of hepatotumorigenesis because decreased AMPK activation is implicated in tumor development and therefore may be a tumor suppressor and a promising target for cancer chemoprevention (38).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, EGCG may also improve metabolic abnormalities by activating AMPK in the liver, which enhances insulin sensitivity and increases fatty acid oxidation but decreases fatty acid synthesis (32). This finding is consistent with recent studies showing that EGCG increases insulin sensitivity and fat oxidation and induces AMPK activity in the liver (36,37). Furthermore, in addition to the improvement of metabolic disorders, activation of AMPK by EGCG also positively contributes to the prevention of hepatotumorigenesis because decreased AMPK activation is implicated in tumor development and therefore may be a tumor suppressor and a promising target for cancer chemoprevention (38).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, our results indicated that ALC did not alone affect Akt phosphorylation significantly, but augment insulin signaling pathway by activating AMPK, which eventually led to Akt activation [24]. Reports concerning interactions between PI-3K/Akt and AMPK are controversial.…”
Section: Discussionmentioning
confidence: 62%
“…Tea is manufactured from the leaves of the plant Camellia sinensis Kuntze (Theaceae) and has been regarded to possess anti-cancer, anti-obesity, antiatherosclerotic, anti-diabetic, anti-bacterial, and antiviral effects (6,12,14,31,33). Many of the beneficial effects of green tea are related to the actions of (−)-epigallocatechin gallate (EGCG), a major component of green tea catechins (14,27,33) (Fig.…”
mentioning
confidence: 99%
“…Many of the beneficial effects of green tea are related to the actions of (−)-epigallocatechin gallate (EGCG), a major component of green tea catechins (14,27,33) (Fig. 1).…”
mentioning
confidence: 99%